Power flow in the air gap of linear electrical machines by utilisation of the Poynting vector: Part 2 ‐ simulations. Issue 9 (20th July 2022) - Frost, Anna E.; Sjölund, Jonathan; Eriksson, Sandra; Leijon, Mats
Abstract: Different types of linear generators are simulated and their power flow in the air gap is investigated. The results are compared to the analytical expressions derived in Part 1. The simulations and the analytical expressions in Part 1 show the same general behaviour, but the magnitudes are lower for the analytical expressions. One explanation for the difference in magnitude can be that the harmonics of the electric and magnetic fields contribute to the power flow, which is not accounted for in the analytical expressions. Due to results from Part 1, it is investigated if changing the number of poles can decrease the tangential power flow while the normal power flow stays the same. As was suspected, changing the number of poles affected several other factors, which lead to an increase in the normal power flow when increasing the number of poles, even though the electrical power was the same. The tangential power flow also decreased for three out of four generators. Thereby, increasing the number of poles while keeping the same length of the machine, at the cost of reduced pole‐pitch, should be done with precaution.